2004
DOI: 10.1124/jpet.103.063453
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Tolerability and Prolonged Prostaglandin Inhibition in the Brain with a Nitric Oxide-Releasing Flurbiprofen Derivative, NCX-2216 [3-[4-(2-Fluoro-α-methyl-[1,1′-biphenyl]-4-acetyloxy)-3-methoxyphenyl]-2-propenoic acid 4-nitrooxy butyl ester]

Abstract: NCX-2216 [3-[4-(2-fluoro-␣-methyl-[1,1Ј-biphenyl]-4-acetyloxy)-3-methoxyphenyl]-2-propenoic acid 4-nitrooxy butyl ester] is anNO-releasing flurbiprofen derivative that also contains a ferulic acid (antioxidant) moiety. NCX-2216 has been shown to be effective in reducing ␤-amyloid deposition in a transgenic mouse model of Alzheimer's disease. The tolerability of this compound in the stomach and its ability to suppress prostaglandin synthesis in the brain are not known. The purpose of this study was to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Overall, our data demonstrate a clear cognitive benefit of long-term administration, but are inconclusive with respect to the relationship between effects on Aβ deposition and behavioural improvements. Previous studies have shown that chronic treatment with nitric oxide-releasing flurbiprofen derivatives do lower Aβ accumulation in APP mice, but it is not clear if this effect is due to the prodrug (which is not likely to affect Aβ42 production) or flurbiprofen released following metabolism [27,53]. In this study we see trends towards reduced Aβ deposition in the prevention studies and small but significant decrease in Aβ deposition in the therapeutic study.…”
Section: Discussionsupporting
confidence: 46%
“…Overall, our data demonstrate a clear cognitive benefit of long-term administration, but are inconclusive with respect to the relationship between effects on Aβ deposition and behavioural improvements. Previous studies have shown that chronic treatment with nitric oxide-releasing flurbiprofen derivatives do lower Aβ accumulation in APP mice, but it is not clear if this effect is due to the prodrug (which is not likely to affect Aβ42 production) or flurbiprofen released following metabolism [27,53]. In this study we see trends towards reduced Aβ deposition in the prevention studies and small but significant decrease in Aβ deposition in the therapeutic study.…”
Section: Discussionsupporting
confidence: 46%
“…Activation of microglia and astrocytes is closely associated with the neuroinflammatory response that contributes to neurodegeneration. In an amyloid transgenic mouse, NCX-2216 was observed to activate microglia in a manner leading to clearance of amyloid, but not to neurotoxic inflammation; and in a further study to inhibit COX-2 expression and prostaglandin synthesis in the rat brain for a prolonged period compared to flurbiprofen, although NCX-2216 was not detected in brain tissue (Wallace et al 2004). Administration of HCT-1026 to amyloid transgenic mice was reported to inhibit microglial activation surrounding plaques (van Groen & Kadish 2005), and a direct comparison of flurbiprofen, HCT-1026 and NCX-2216 in adult rats injected in the nucleus basalis with Aβ 1–42 , showed a reduction in inflammatory markers including iNOS (Prosperi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Peak levels in the CSF occur between 1 and 3 h for flurbiprofen in the rat (Matoga et al . 1999; Wallace et al . 2004) and at 3 h for ibuprofen in humans (Bannwarth et al .…”
Section: Clinical Relevance Of Non‐cox Mediated Effects Of Nsaids: Camentioning
confidence: 99%
“…1995) and their levels rapidly decline thereafter. Interestingly, one NO‐releasing derivative of flurbiprofen, NCX 2216, shows a long‐lasting suppression of prostaglandin production in the brain and CSF (Wallace et al . 2004).…”
Section: Clinical Relevance Of Non‐cox Mediated Effects Of Nsaids: Camentioning
confidence: 99%
See 1 more Smart Citation